Simple synthetic route to an enzyme-inspired transesterification catalyst. Issue 22 (2nd November 2022) - Kumar, Ashwani; Nothling, Mitchell D.; Aitken, Heather M.; Xiao, Zeyun; Lam, Matthew; Bell, Craig A.; O'Mara, Megan L.; Connal, Luke A.
Abstract : Self-assembling transesterification catalyst inspired by the catalytic triad. Abstract : Inspired by the chemical structure of chymotrypsin, we report an artificial catalytic triad with high catalytic efficiency for the transesterification reaction of vinyl trifluoroacetate and methanol. Rate accelerations of ( k cat / k unc ) 4.81 × 10 4 -fold over the background reaction were observed. We highlight a simple two step synthetic approach to incorporate three functional groups (–OH, –CO2 H, –imidazole) on a single molecule, similar to native enzymes like chymotrypsin. The addition of a hydrophobic chain furnishes amphiphilic catalysts that form clusters for reactions in organic solvents. The cluster formation was studied using molecular dynamics (MD) simulations, dynamic light scattering (DLS) and 1 H NMR, revealing complex H-bonding interactions between the catalytic head groups of the artificial catalytic triad, drawing similarities to native enzymes.